Development of Ethnomathematics-Based Digital Modules Inspired by Bima Traditions to Enhance Middle School Students’ Geometry Problem-Solving Skills - ., Andang; ., Sowanto; Hadi, Arnasari Merdekawati; Akbarini, Nur Rahmi; Budiyono, Fajar; Fitrah, Muh; Mulyadin, Edi; ., Juryatina (Journal of Posthumanism, 2025)
This study explores the integration of ethnomathematics-based digital learning materials to enhance students’ problem-solving abilities in geometry. The research focuses on developing an interactive e-module incorporating Bima’s cultural elements, such as tembe nggoli, sarau, uma lengge, and mpa’a gopa, to create a contextual learning experience. A quasi-experimental design was applied, comparing students using the e-module with those using conventional printed modules. The findings indicate that the experimental group achieved a significantly higher post-test score (M = 4.0223, SD = 1.25488) than the control group (M = 2.9784, SD = 1.18472), as confirmed by an independent t-test (p < 0.05). These results highlight the effectiveness of integrating cultural contexts into geometry learning, improving students’ comprehension, motivation, and engagement. Interviews with teachers and students further emphasize the e-module’s alignment with students’ digital learning habits, making mathematical concepts more accessible.